Tubular image states: General formulation and properties for metallic and nonmetallic nanotubes - Segui Osorio, Silvina Inda Maria (2012)
In this work we study the existence of image potential states around nanotubes by considering the interactionbetween a stationary charged particle and a polarizable cylinder of infinite length. For metallic nanotubes andwires we obtain the eigenstates and eigenenergies corresponding to nonzero angular momentum states, localizedat a relatively long distance from the surface of the tube. We study the scaling properties of the system in orderto define general conditions for which image states can be supported. We also analyze the case of nonmetallicarbon nanotubes, for which we do not obtain bound states.